Development of a multi-layer microelectrofluidic platform - Ng, S. H.; Wang, Z. F.; Tjeung, R. T.; de Rooij, Nicolaas F. (My University, 2007)
We report on recent advances in micro fabrication technology using micromoulding and high-aspect ratio structuring of photopolymer. The direct application is the realization of components for millimeter-size, ultrasonic piezoelectric motors. A new fabrication process using a thick epoxy-based material (SU-8) and the electroplating of nickel is demonstrated. Photopolymer structures have also been realized and released using a positive tone resist as sacrificial layer. The main advantages over past fabrication methods are better design flexibility, simplicity of the fabrication process, the capability to combine metallic materials (Ni) with polymeric materials (SU-8), and the use of positive tone resist as a sacrificial layer.